Design of a continuously and linearly controlled VSI-based STATCOM for load current balancing purposes - Faris Asaad Abdulmunem; Abdulkareem Mokif Obais (Institute of Advanced Engineering and Science, 2021)
In this paper, load current balancing are reviewed in both three-wire and 4-wire systems taking into account linearity, harmonics injection, and control schemes. A linearized static compensator (STATCOM) based on H-bridge voltage source inverter (VSI). The proposed STATCOM is controlled in closed loop mode via equipping it with a new current controller. The DC capacitor voltage of the STATCOM is kept constant without using external energy injection or storage devices via shunting the DC capacitor with a suitable series filter. The simulation results of the current responses of the 220V, 50Hz STATCOM reveal continuous and linear performance during responding to reactive current demands from 123A inductive current to 227A capacitive current. The transition time required for the proposed STATCOM during treatment of a sudden change in reactive current demand from maximum inductive current to maximum capacitive current is less than 40ms. The steady state portions of the STATCOM current responses show pure sinusoids, thus the proposed STATCOM can be promoted as harmonic free static Var compensator. The closed loop continuous mode control and the considerable linearity of the proposed STATCOM promot it as a bipolar susceptance (capacitive and inductive) in applications of load current balancing systems in both three and four wire power systems.